Kehamilan Tidak Direncanakan dalam Keluarga Patriarkal: Sebuah Scoping Review - Purnamasari, Arryan Rizqi Aulia; Wuri Astuti, Andari; anjarwati, anjarwati (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Unintended pregnancy is a global issue that threatens women's physical and mental health, with 50% of pregnancies worldwide falling into this category, largely influenced by male dominance in decision-making. In patriarchal families, women often lose their reproductive decision-making rights, increasing health risks and gender-based violence. Objectives: The purpose of this scoping review is to analyze women's experiences in facing unintended pregnancies within patriarchal families. Methods: The method used involved searches across four databases PubMed, Wiley, Science Direct, and Google Scholar using the PRISMA ScR methodology. Data were collected based on research objectives, publication year, study design, respondent characteristics, and research context. Critical appraisal was conducted using the JBI Critical Appraisal Tools. Results: This scoping review analyzed five qualitative studies from South Asia (Bangladesh, Pakistan, Nepal) and Africa (Eswatini, Nigeria) related to unintended pregnancy in patriarchal families. Based on the assessment, two articles were categorized as Grade A, while three were categorized as Grade B. The analysis identified three main themes: male-dominated decision-making patterns, gender inequality in contraceptive use and gender literacy, and the role of families in either supporting or opposing unintended pregnancies, including abortion decisions. Conclution:Unintended pregnancy in patriarchal families reflects the complexities of male dominance, gender inequality, and the lack of family support, which undermine women's rights, autonomy, and well-being.